The relation between female teenagers' life style and osteoporosis prevention - Z Rahnavard; M Zolfaghari; A Kazemnejad; L Zarei (Tehran University of Medical Sciences, 2006)
Background & Aim: Some aspects of life style in adulthood have major preventive role from osteoporosis in adult ages. This research has been done in order to determining female teenager's life style in relation with prevention of osteoporosis. Methods & Materials: This research was a descriptive - analytical study. In this study, 760 person of female teenage students in high schools and pre-university centers of zone 17 in Tehran city were chosen by random classified cluster sampling method. In this study, the tool for data collection was written questionnaire, and method of it was answering to questionnaire. The questionnaire had 2 parts. First part included demographic characteristics, and second part included different dimensions of lifestyle in relation with prevention of osteoporosis, such as nutrition, exercise and physical activity, habits (smoking, using weight loss food regimen and weight loss drug). The life style categorized as 3 levels unfavorable, partially favorable, and favorable. The collected information was assessed by SPSS software and descriptive and analytical statistical methods were used to reaching study objects. Results: Results Showed nutrition, phisycal activity and exercise the highest percent of cases (51.8%, 57.7%) had undesirable lifestyle. Also 50 percent of cases had undesirable lifestyle. About habits (Smoking, using weight loss food regimen and using weight loss drug) the highest percent of cases (74.9%) had desirable lifestyle. Also there was a significant statistical relationship between life style and variables of education level (p=0.004), economical status of family (p=0.043), the birth number in family (p=0.001) and educational level of mother (p=0.005). Conclusion: According to the results of research, lifestyle of 50% of female teenagers was undesirable. Findings of this research are attentive and need more assessment and planning by responsible people in order to omitting noted problems in lifestyle.